IP Subnetting from Beginning to Mastery - Odom, Wendell (Cisco Press, 2020)
12+ Hours of Video Instruction Overview Learn Subnetting, Do Subnetting, Master Subnetting: Big Ideas, Key Calculations, and How to Go Fast Overview To build the networks used throughout the world you must understand the single most important networking protocol: Internet Protocol, or IP. IP itself has several components, most notably IP addressing, IP routing, IP routing protocols, and of course, IP subnetting. Unfortunately, learning IP subnetting can be a big challenge. For example, IP subnetting includes many interwoven ideas. Many common tasks in networking require knowledge of those fundamentals. However, output and figures that describe IP networks do not describe the underlying concepts; they just list the numeric facts about addresses and subnets. Without proper background knowledge, people can struggle to connect the facts to the ideas and make the correct conclusions. Additionally, subnetting math causes the kinds of challenges to both new learners and long-time IT practitioners. Subnetting math works a lot like math word problems did for us all back in school. Thankfully, all the subnetting math can be understood with a little explanation and practice. However, subnetting includes enough different ideas, terms, and math processes so that you might struggle in choosing what number you need to find, what math process to use, and what the results mean once calculated. This complete IP Version 4 (IPv4) Subnetting course sets out to solve these problems. The course works through a series of topics about some big ideas, followed by the related subnetting math, and then with available practice for you to build the skill level you need for your purposes. No matter your motivation or current job role, this course helps you: Learn subnetting: Understand the ideas and terms in each part of IPv4 subnetting, how to use the ideas in the related mathematical processes, and the purpose and meaning of the facts learned by those processes. Do subnetting : Work through a sequence to first learn by seeing the process, and then transition to doing the process through practice problems with video explanations, internalizing the process so you can do it on your own. Go faster at subnetting: For those who work with subnetting math every week, or who are studying for certification exams, you need to also practice to the point of going fast at these processes. The course discusses speed goals, how to practice for speed, and how to set reasonable speed expec ...